2020
DOI: 10.18231/j.tjp.2020.005
|View full text |Cite
|
Sign up to set email alerts
|

School refusal - Psychosocial distress or Psychiatric disorder?

Abstract: Background: School refusal is not a diagnosis by itself but a behavior described when a child frequently refuses to go to school or remain in school. It is often associated with several psychiatric disorders. A prevalence rate of 5-10% is described in most studies. Several psychosocial factors, individual, familial, societal, school and medical are also known to play an important role. The study intends to explore the association of school refusal to either psychiatric disorder or to distress due to psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…8, 10 Other factors, including an account of abuse, adoption, stepmother, and issues with peers, influence school refusal behavior. 10 However, contrary to other studies, Fukuya et al found that child rearing, such as parent–child dealings and child maltreatment, may not be associated with school refusal among elementary school pupils. 7 Differences in study design and cultural differences in parenting and child-rearing practices may account for this discrepancy in findings.…”
Section: School Refusal: Key Conceptsmentioning
confidence: 99%
See 3 more Smart Citations
“…8, 10 Other factors, including an account of abuse, adoption, stepmother, and issues with peers, influence school refusal behavior. 10 However, contrary to other studies, Fukuya et al found that child rearing, such as parent–child dealings and child maltreatment, may not be associated with school refusal among elementary school pupils. 7 Differences in study design and cultural differences in parenting and child-rearing practices may account for this discrepancy in findings.…”
Section: School Refusal: Key Conceptsmentioning
confidence: 99%
“…7,8 In India, several studies have reported a prevalence rate of up to 7%. 9,10 Research indicates that school refusal peaks around the age of transition between school stages at the start of primary school or after the move to secondary school and is more common in secondary-age pupils. [11][12][13] Some studies have found a significant association between school refusal and socio-demographic aspects like the gender of the children, family type, regular income of families, and parental education.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…CSA is associated with a high degree of school dropout, poor psychological wellbeing and physical health, poor academic performance as well as social development [ 14 ]. Additionally, CSA exacerbates the risk of non-participation in the workforce, and subsequent long-term poverty [ 7 , 15 – 17 ]. CSA is influenced by a combination of individual, family, and social factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%